2015
DOI: 10.2983/035.034.0231
|View full text |Cite
|
Sign up to set email alerts
|

Is Copper Supplementation Required in Formulated Feeds forOctopus vulgaris(Cuvier, 1797)?

Abstract: The aim of this study was to test the effect of copper supplementation in a formulated feed on the growth, feed efficiency, and nutritional composition of subadults Octopus vulgaris, with particular reference to the differences in the content of copper in the tissues (muscle, digestive gland, and hemolymph). Two formulated feeds were supplied to subadults octopuses kept individually for 56 days: Basal diet [11.6 mgCu/kg dry weight (dw)], and another feed with a similar composition but including a copper supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Supporting this idea, some studies conducted in cuttlefish ( Sepia officinalis ) embryo shown increased PO activity after exposure to dissolved metals (Lacoue-Labarthe et al, 2009), while O. vulgaris infected by a protozoan parasite show changes in blood Hc (Castellanos-Martinez et al, 2014). In the present study, plasma Hc reached stable values circa 1–1.5 mM in all animals after 24 h recovery, similar to those levels described in several cephalopod species (Senozan et al, 1988; Aguila et al, 2007; Sancho et al, 2015; Roumbedakis et al, 2017). Our hypothesis that Hc acts as a total PO-like enzyme in octopus is based in the fact that after bottom trawling E. moschata and O. vulgaris had 60–80% less Hc and pro-PO activity than 24 h later, when recovered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Supporting this idea, some studies conducted in cuttlefish ( Sepia officinalis ) embryo shown increased PO activity after exposure to dissolved metals (Lacoue-Labarthe et al, 2009), while O. vulgaris infected by a protozoan parasite show changes in blood Hc (Castellanos-Martinez et al, 2014). In the present study, plasma Hc reached stable values circa 1–1.5 mM in all animals after 24 h recovery, similar to those levels described in several cephalopod species (Senozan et al, 1988; Aguila et al, 2007; Sancho et al, 2015; Roumbedakis et al, 2017). Our hypothesis that Hc acts as a total PO-like enzyme in octopus is based in the fact that after bottom trawling E. moschata and O. vulgaris had 60–80% less Hc and pro-PO activity than 24 h later, when recovered.…”
Section: Discussionsupporting
confidence: 90%
“…Animals were anesthetized by decreasing water temperature to circa 4°C (by covering the aquariums with ice for 5 min, without physical disturbance of the animals) and addition of 2.5% ethanol for 2 min after that, conforming the principles of Directive 2010/63/EU, and following described procedures (Malham et al, 2002; Estefanell et al, 2011; Sancho et al, 2015). Haemolymph samples were taken with sterile 1 mL 25 G syringes (circa 300 μL per animal) from the principal heart as described before (Aguila et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Altogether, these results might suggest that O. vulgaris has a limited tolerance to high-lipid feeds during prolonged periods, as the two referred studies (Morillo-Velarde et al [10] and Rodríguez-González et al [54]) and the present showed this FE reduction and share the commonality of feeding octopus on high-lipid diets. The higher metabolic effectiveness of smaller animals, compared with bigger ones, should also explain the decrease in FE during the second month [6,58]. Although the individuals used in the experiment were males (known to be less affected by reproduction processes), maturation could also have affected FE.…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to this metal either triggering or inhibiting the phenoloxidaselike activity, which is implicated in the innate immune system (Lacoue-Labarthe et al 2009). On the other hand, 6 ppm of copper in seawater (used as a way to increase the availability of this trace element) has been used in O. vulgaris paralarvae rearing (Garrido et al 2014) or even up to 115 ppm in formulated feeds for juveniles of this same species (Sancho et al 2015) without deleterious effects. The differences found between S. officinalis and O. vulgaris might be due to the possibility of this trace element being essential for the proper development of the latter, as suggested by Villanueva and Bustamante (2006) and García--García and Cerezo-Valverde (2006).…”
Section: Egg Infections and Cephalopods Malformationsmentioning
confidence: 99%